2008
DOI: 10.5194/bg-5-433-2008
|View full text |Cite
|
Sign up to set email alerts
|

Quality control of CarboEurope flux data – Part 1: Coupling footprint analyses with flux data quality assessment to evaluate sites in forest ecosystems

Abstract: Abstract. We applied a site evaluation approach combining Lagrangian Stochastic footprint modeling with a quality assessment approach for eddy-covariance data to 25 forested sites of the CarboEurope-IP network. The analysis addresses the spatial representativeness of the flux measurements, instrumental effects on data quality, spatial patterns in the data quality, and the performance of the coordinate rotation method. Our findings demonstrate that application of a footprint filter could strengthen the CarboEur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
142
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(149 citation statements)
references
References 66 publications
2
142
0
5
Order By: Relevance
“…For wind sectors parallel to the shoreline, 95 % of the residual mean vertical wind velocity stays within ±0.12 ms −1 . These values stay within acceptable limits, compared to a multi-site quality analysis by Göckede et al (2008).…”
Section: Coordinate Rotation and Footprint Analysismentioning
confidence: 80%
See 2 more Smart Citations
“…For wind sectors parallel to the shoreline, 95 % of the residual mean vertical wind velocity stays within ±0.12 ms −1 . These values stay within acceptable limits, compared to a multi-site quality analysis by Göckede et al (2008).…”
Section: Coordinate Rotation and Footprint Analysismentioning
confidence: 80%
“…The footprint analysis includes not only the calculation of the footprint, but also the spatial distribution of flux quality according to Göckede et al (2008), which enables the user to identify spatial patterns such as obstacles or heterogeneities contributing to the quality of the measured fluxes. In our study no such patterns could be identified for either station.…”
Section: Coordinate Rotation and Footprint Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Data-quality selection criteria were applied in this study in order to examine time series of fluxes and generate a high-quality database [24]. The internal boundary layer estimation and footprint analysis were performed so as to compute the contribution from the target surface [25,26]. In the rice field, the fetch ranged from 37 m (northwest) to 60 m (northeast), generating the internal boundary layer height ranging from 3.0 m to 3.9 m and 68% to 82% of the flux contributed by the rice field.…”
Section: Research Sites and Field Campaignsmentioning
confidence: 99%
“…Flux footprint climatology is a practical method to illustrate the portion of the sampled landscape that contributes the most to EC vertical turbulent flux at a given point over long-term periods (Amiro, 1998;Kljun, 2010a;Cai et al, 2011;Aubinet et al, 2012;Zhang et al, 2012). This method is used to understand carbon budgets, assess the quality of EC data, and upscale the representativeness of a tower flux to regional or global scales (Rebmann et al, 2005;Göckede et al, 2008;Chen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%